Attenuation of oxidative damage and inflammatory responses by apigenin given to mice after irradiation - Rithidech,K.N. (Elsevier, 2015)
We determined the in vivo efficacy of apigenin, as an anti-oxidant and anti-inflammatory agent, given to mice after irradiation. Various concentrations of apigenin (0, 10, 20, and 40mg/kg body weight) were administered to mice by a single intraperitoneal injection 3hr after receiving 0 or 3Gy of 137Cs gamma rays. Mice receiving vehicle only (no radiation and no apigenin) served as sham controls. We assessed the anti-oxidative activity of apigenin in vivo by measuring levels of 8-hydroxy-2-deoxy guanosine (8-OH-dG) in bone marrow (BM) cells, collected at days 3 and 10 after irradiation, from groups of mice (5 mice per treatment group) with or without apigenin treatment. Simultaneously, we evaluated the ability of apigenin to diminish radiation-induced inflammatory responses in bone-marrow-derived macrophages (BMDMs) from the same individual mice used for measuring the level of 8-OH-dG. To do this, the levels of activated nuclear factor-kappa B (NF-kappa B) and NF-kappa B-regulated pro-inflammatory cytokines [i.e. interleukin 1-beta (IL-1beta), IL-6, and tumor necrosis factor-alpha (TNF-alpha)] were measured in BMDMs. Our results indicated significant reductions (p<0.01 or <0.05) in the levels of 8-OH-dG in BM cells collected at both harvest times from irradiated mice receiving apigenin treatment, at all apigenin concentrations tested. Likewise, activation of NF-kappa B in BMDMs collected from gamma-irradiated mice that received apigenin was suppressed at both harvest times. Further, the levels of pro-inflammatory cytokines in gamma-irradiated mice treated with 20 or 40mg/kg body weight apigenin were significantly lower than those in mice receiving radiation only (p<0.01 or <0.05) even at day 10 post-irradiation. Additionally, the ratio of neutrophils to lymphocytes indicated that apigenin ameliorated radiation-induced hematological toxicity. Our study is the first to demonstrate the mitigative/therapeutic effects of apigenin given to mice after irradiation. © 2012 Elsevier B.V.